2021
DOI: 10.1002/ajim.23293
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for the duration until return to work after surgery for work‐related rotator cuff syndrome: A prospective study of 92 workers

Abstract: Background Return to work (RTW) after surgery for a work‐related rotator cuff disorder (WRRCD) is often difficult. The study's purpose was to identify preoperative factors predicting RTW. Methods Ninety‐two workers with a WRRCD were identified by four surgeons. Before surgery, the workers completed a series of standardized questionnaires related to working conditions, health, and health beliefs. They were followed up prospectively for 20 months. Statistical analysis was based on single and multiple‐factor Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In addition to physically strenuous work, older age and workers’ compensation status increase the likelihood of unsatisfactory outcomes after aRCR. 4,6,27,30 Attempts to summarize these findings prove difficult, as it is difficult to accurately capture what truly drives poor outcomes. Is it the poor tissue quality secondary to advanced patient age, high rotator cuff demand upon return to work, secondary gain because of a workers’ compensation claim, or some combination thereof?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to physically strenuous work, older age and workers’ compensation status increase the likelihood of unsatisfactory outcomes after aRCR. 4,6,27,30 Attempts to summarize these findings prove difficult, as it is difficult to accurately capture what truly drives poor outcomes. Is it the poor tissue quality secondary to advanced patient age, high rotator cuff demand upon return to work, secondary gain because of a workers’ compensation claim, or some combination thereof?…”
Section: Discussionmentioning
confidence: 99%
“…As a single unifying definition for manual labor has not been established, manual labor was defined as any job that requires physical strength, such as heavy lifting or prolonged heavy use of the operative shoulder. 6,14,23,28,30,32 All the professions included in this study, according to the Bureau of Labor Statistics, required heavy lifting and high levels of upper body strength. 28 Degree of shoulder use was further stratified according to the Canadian Classification and Dictionary of Occupations to fully capture patient-specific shoulder use within his or her profession.…”
Section: Patient Populationmentioning
confidence: 99%
“…However, in the multivariable analysis, active workload was significantly associated with unsuccessful return to work (P ¼ .034), whereas preoperative participation in shoulder-related sports was associated with successful return to work (P ¼ .016). Previous studies have identified heavy physical labor, 9,16,18,20,22,38 involvement of the dominant arm, 16,18 older age, 11,22 female sex, 9 less participation in sports, 22 and low postoperative PROMs 16,36 to be associated with poor return to previous work after rotator cuff repair. The findings of this study are consistent with those of these previous studies and additionally identified preoperative participation in shoulder sports as an independent factor that aids successful return to previous work.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several studies have found that patients who had more physically intensive jobs before sustaining rotator cuff tears were less likely to return to work after an arthroscopic rotator cuff repair. 1,5,12,13,15,23 Aagaard et al 1 and Gutman et al 12 found that patients who sustained rotator cuff tears on the side of their dominant arm were less likely to return to work than were patients who sustained tears on their nondominant side. Collin et al 5 and Imai et al 15 found that female patients were less likely to return to work after a rotator cuff repair y than were male patients.…”
mentioning
confidence: 99%
“…Specifically, several studies have found that patients who had more physically intensive jobs before sustaining rotator cuff tears were less likely to return to work after an arthroscopic rotator cuff repair. 1 , 5 , 12 , 13 , 15 , 23 …”
mentioning
confidence: 99%